Coexistence of Hashimoto's thyroiditis and papillary thyroidal carcinoma with papillary carcinoma of thyreoglossal duct - Čizmić Milica; Ignjatović Mile; Cerović Snežana; Ajdinović Boris (Vojnosanitetski Pregled)
Background. Simultaneous presence of Hashimoto's thyroiditis and papillary thyroidal carcinoma in thyroidal gland with papillary carcinoma association in thyroglossal duct is quite rare. The questions like where the original site of primary process, is where metastasis is, what the cause of coexisting of these diseasesis present a diagnostic dilemma. Case report. We presented a case of a 53-year old female patient, with the diagnosis of Hashimoto's thyroiditis and symptoms of subclinical hypothyreosis and nodal changes in the right lobe of thyroidal gland, according to clinical investigation. Morphological examination of thyroidal gland, ultrasound examination and scintigraphy with technetium (Tc) confirmed the existence of nonhomogenic tissue with parenchyma nodular changes in the right lobe of thyroidal gland that weakly bonded Tc. Fine needle biopsy in nodal changes, with cytological analyses showed no evidence of atypical thyreocites. Hashimoto's thyroiditis was confirmed on the basis of the increased values of anti-microsomal antibodies, the high levels of thyreogobulin 117 ng/ml and TSH 6.29 μIU/ml. The operation near by the nodular change in the right lobe of thyroidal gland revealed pyramidal lobe spread in the thyroglossal duct. Total thyroidectomia was done with the elimination of thyroglossal duct. Final patohystological findings showed papillary carcinoma in the nodal changes pT2, N0 and in the thyroglossal duct with the presence of Hashimoto's thyroiditis in the residual parenchyme of the thyroid gland. After the surgery the whole body scintigraphy with iodine 131 (131I) did not reveal accumulation of 131I in the body, while the fixation in the neck was 1%. After that, the patient was treated with thyroxin with suppressionsubstitution doses. Conclusion. Abnormality in embrional development of thyroidal tissue might be the source of thyroidal carcinoma or the way of spreading of metastasis of primary thyroidal carcinoma from thyroid gland. The cause of this process is most probably a hereditary mutation in RET oncogenes.